Simultaneous detection of copper and mercury in water samples using in-situ pH control with electrochemical stripping techniques. (20th January 2023) - Patella, Bernardo; Narayan, Tarun; O'Sullivan, Benjamin; Daly, Robert; Zanca, Claudio; Lovera, Pierre; Inguanta, Rosalinda; O'Riordan, Alan
Highlights: Electrochemical sensor for heavy metal quantification in water samples without pretreatments. The local pH can be adjusted by tailoring the applied potential to the protonator electrode. Very low LOD for Cu and Hg were demonstrated with extremely high sensitivity. This technique allowed detection of these metals in river water, without sample pretreatment. In-situ pH control can allow heavy metal in real time and in situ analysis by unskilled personnel in remote settings. Abstract: The performance of electrochemical sensors using an in situ pH control technique for detection of mercury and copper in neutral solutions is described herein. Sensors are comprised of two distinct parallel gold interdigitated microband electrodes each of which may be polarised separately. Biasing one interdigitated "protonator" electrode sufficiently positive to begin water electrolysis, resulted in the production of H + ions, which, consequently droped the interfacial pH at the other second interdigitated "sensing" electrode. This decrease in pH permitted the electrodeposition (and consequent stripping) of metals at a sensing electrode without the need to acidify the whole test solution. In this work, the local pH could be adjusted in the acidic pH range in a stable and reproducible way just by tailoring the polarization of the protonator electrode. Using this approach, a linear range for copper 5 to 100 ppb and for mercury 1 to 75 ppb were obtained. The sensors also have an extremely high sensitivity for the metals. The in-situ pH control, coupled with electrochemical stripping, allowed metal detection in a complex water matrix, e.g., river water without the need for sample pre-treatment. The electrochemical results were confirmed by comparison to those obtained using inductively coupled plasma – optical emission spectroscopy. A very good agreement was observed between both sets of results. The electrode reproducibility was high (RSD < 10%) and the metals could be co-detected simultaneously. Thus, this work shows a fast and easy approach for in-situ pH control for multi metal detection using solid state sensors.